2008
DOI: 10.1177/1753193408090148
|View full text |Cite
|
Sign up to set email alerts
|

The Non-Dissociative Clunking Wrist: A Personal View

Abstract: Clunking of the wrist is often the result of a combined radiocarpal and midcarpal ligament insufficiency, coupled with inadequate neuromuscular coordination. When symptomatic, these wrists may benefit from splinting, isometric exercising of specific muscles and advice on activity modification. Failing this, different surgical strategies have been proposed, depending on the location of dysfunction. When the clunking derives from an isolated injury of one joint, reconstruction of its inadequate ligaments may be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 62 publications
(99 reference statements)
0
73
0
5
Order By: Relevance
“…Given that climbers present a stronger imbalance, it is probable that they have more difficulties in controlling and protecting their joints and are, therefore, more exposed to joint instability, joint surface over-use and/or ligament tears (Centomo et al 2008;Stokes and Gardner-Morse 2003). This finding could explain why wrist medio-carpal instability (Garcia-Elias 2008;Lichtman et al 1981;Lichtman and Wroten 2006) is often observed in climbers, although no medical reports have been published recently. This important imbalance may also be implicated in finger pulley ruptures, since the extensor muscle action is also required during the crimp grip technique .…”
Section: Discussionmentioning
confidence: 75%
“…Given that climbers present a stronger imbalance, it is probable that they have more difficulties in controlling and protecting their joints and are, therefore, more exposed to joint instability, joint surface over-use and/or ligament tears (Centomo et al 2008;Stokes and Gardner-Morse 2003). This finding could explain why wrist medio-carpal instability (Garcia-Elias 2008;Lichtman et al 1981;Lichtman and Wroten 2006) is often observed in climbers, although no medical reports have been published recently. This important imbalance may also be implicated in finger pulley ruptures, since the extensor muscle action is also required during the crimp grip technique .…”
Section: Discussionmentioning
confidence: 75%
“…In cases of patellar maltracking, abnormal motion is present at some point of the first 30 • of knee flexion when the patella engages the trochlea. Similarly, in cases of midcarpal instability there is abrupt, abnormal motion of the whole first carpal row at some point of radio-ulnar deviation or dart throwing maneuver [20]. In the wrist, there are variations in bone position (or angulation) that are specific of a motion path, a phenomenon called hysteresis.…”
Section: Dynamic Ctmentioning
confidence: 98%
“…Again several additional views are described as being helpful. GarciaElias describes the forced ulnar and radial deviation and the anterior and posterior drawing views to determine ligament laxity (Garcia-Elias 2008). The absence of normal values for these views and the degrees of laxity in healthy subjects without wrist pain make the use of these views in general practice debatable.…”
Section: Type II Instabilitiesmentioning
confidence: 99%
“…If this is painful the test is called positive and is considered a diagnostic indicator of a symptomatic midcarpal instability. The anterior and posterior drawer tests as described by Garcia-Elias (2008) are also important. The anterior drawing test is aimed at demonstrating laxity of the palmar ligaments especially the scaphotrapezial ligament; the posterior drawer test, in which the hand is translated dorsally compared to the wrist stresses the dorsal ligaments, especially the dorsal scaphotriquetral ligament.…”
Section: Cineradiographymentioning
confidence: 99%
See 1 more Smart Citation